2022
DOI: 10.1055/a-1843-9788
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Immunotherapeutic Potential of Oleocanthal against Murine Cutaneous Leishmaniasis

Abstract: Leishmaniasis is a major tropical disease with increasing global incidence. Due to limited therapeutic options with severe drawbacks, the discovery of alternative treatments based on natural bioactive compounds is important. In our previous studies we have pointed out the antileishmanial activities of olive tree-derived molecules. In this study, we aimed to investigate the in vitro and in vivo antileishmanial as well as the in vivo immunomodulatory effects of oleocanthal, a molecule that has recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…At this point, it must be highlighted that OLEA and OLEO comprise derivatives (precursors) of HT and T, respectively, and could facilitate as prodrugs releasing HT and T in a biological system after metabolization (hydrolysis). These findings are consistent with one of our previous studies, which demonstrated the remarkable in vitro and in vivo anti-leishmanial properties of pure OLEO [ 26 ]. Moreover, this is the first study that describes the nature of interactions between the phenolic extracts of EVOO and miltefosine against both a viscerotropic and a dermotropic Leishmania strain.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…At this point, it must be highlighted that OLEA and OLEO comprise derivatives (precursors) of HT and T, respectively, and could facilitate as prodrugs releasing HT and T in a biological system after metabolization (hydrolysis). These findings are consistent with one of our previous studies, which demonstrated the remarkable in vitro and in vivo anti-leishmanial properties of pure OLEO [ 26 ]. Moreover, this is the first study that describes the nature of interactions between the phenolic extracts of EVOO and miltefosine against both a viscerotropic and a dermotropic Leishmania strain.…”
Section: Discussionsupporting
confidence: 94%
“…According to the EU Health Claim Labeling Regulation, olive oil polyphenols are therefore listed among food substances with attributed health claims (432/2012) [ 21 , 22 ]. Our group has showcased the anti-leishmanial properties of olive oil phenolic compounds by demonstrating that pure oleuropein and oleocanthal (OLEO) exert anti-leishmanial properties in vitro and promote in vivo efficacy in murine experimental models of VL and CL [ 23 , 24 , 25 , 26 ]. In addition, we have reported that TPF exhibits chemotherapeutic anti-leishmanial activity in vitro and in vivo [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, oleocanthal ( 1 ) was administered IP at the concentration of 5 mg/kg to mice. The indicated dose and method of administration were selected according to literature data and the most used study design in in vivo studies of 1 , to generate meaningful metabolism-related data that could be extrapolated to the claimed effects. Additionally, the time points of the study (0, 5, 15, and 30 min and 1, 4, 6, 8, 12, and 24 h) were a basic element of the current study design.…”
Section: Resultsmentioning
confidence: 99%